If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/5(3x+12)=3(1-4x)+12
We simplify the equation to the form, which is simple to understand
1/5(3x+12)=3(1-4x)+12
Simplifying:
+ 0.2*(3x+12)=3*(1-4x)+12
Reorder the terms in parentheses
+( + 0.6x+2.4)=3*(1-4x)+12
Remove unnecessary parentheses
+ 0.6x+2.4=+3+*(+1-4x+)+12
Reorder the terms in parentheses
+ 0.6x+2.4=+(+3-12x)+12
Remove unnecessary parentheses
+ 0.6x+2.4=+3-12x+12
We move all terms containing x to the left and all other terms to the right.
+ 0.6x+12x=+3+12-2.4
We simplify left and right side of the equation.
+12.6x=+12.6
We divide both sides of the equation by 12.6 to get x.
x=1
| -x+4=5x+22 | | 2k+1=4 | | 6x+14=-51-7 | | c=0.10x+6 | | k(2.2)+k(1.8)+5=15 | | 12x=x/3 | | 6x+10=10x+2+5+1 | | 1/3(x+3)=1/6(2x+6) | | 6x+10=10x | | x+7/4=2x-7/4 | | 6x+7=3+8x-6 | | 22p-72=16-22p | | 11x-7x=-2 | | 3-6=2 | | x(3x)-5x=2 | | 5(y-3)=5-3y | | -(2x-1)=-5(2x+9) | | 1/8(x+8)=1/24(3x+24) | | 3x+5/4=4x-5/4 | | 3x-5(2x-1)=2(4x+7) | | g(2)=x^2-x | | 9x+27-6x+12=60 | | 6x+5=6x+21 | | -2x-10=6x+14 | | 1/3(4x+2)=2(3-4x)+4 | | 8x+30=5x+105 | | -0.03x=1.72x+1.75 | | 5=-1/2(2X-4)-2X | | 5x+14+x=3x-7 | | 8x+7=8(x-1) | | -6x-12=3x+15 | | 6(x-7)=3x |